VIEWS ON THE MANIFESTATION OF LOCAL WISDOM (CASE: KAMPUNG NAGA, WEST JAVA) - Agus Saladin; Agus Budi Purnomo; Sri Tundono (International Journal on Livable Space, 2018)
AbstractThe physical object of architecture is a manifestation of thoughtful concept of the architect. Philosophically, in vernacular architecture, the concept of thoughts is being revealed in the form of local wisdom. Kampung Naga, as one of the vernacular villages in West Java, maintains its traditional culture although the inhabitants have undergone modern thought. The modern era has developed immensely which could affect the decline in preserving the local wisdom. To anticipate the decline, it is necessary to make an effort to formulate the local wisdom which is still existed. This paper aims to explain the results of research in Kampung Naga which focusing on physical elements and accommodating the results of previous research concerning on local wisdom. Data and information as written materials were obtained through field survey, literature review, and previous research studies. The results of the study show that local wisdom in Kampung Naga has an effect on the aspects of life in terms of social interaction, land law, physical building ideas and its spatial order. The paper will be ended with the diagrammatic conceptual model of the aspects of the manifestation of local wisdom in Kampung Naga. Keywords: manifestation, local wisdom, Kampung Naga